Legal Certainty of The Positive Fictive Policy In Business Licensing Through The Online Single Submission Risk-Based Approach System In Indonesia - Nurhayati, Nunik; Giftian Fajri Rustyono; Achmad Miftah Farid; Rohmad Suryadi (Magister Hukum Universitas Semarang, 2025)
This study aims to analyze the positive fictitious licensing policy under the Job Creation Law and assess its legal certainty using Gustav Radbruch’s philosophical framework. The background of this research arises from Indonesia’s legal reform agenda to streamline licensing through the OSS-RBA system. However, this reform raises concerns regarding legal certainty and institutional accountability. The urgency of this study lies in the regulatory ambiguity, lack of procedural safeguards, and removal of judicial oversight. Using a normative juridical method with statutory and conceptual approaches, the study finds that the current policy does not fully meet Radbruch’s four standards of legal certainty. Specifically, it suffers from unclear legal norms, insufficient factual grounding, unstable legal framework, and weak institutional implementation—such as the absence of a Presidential Regulation, undefined verifier responsibilities, and lack of integration between central and local systems. The study concludes that the positive fictitious mechanism needs substantial normative refinement to ensure fairness, transparency, and predictability. The novelty of this research lies in its philosophical approach to evaluating administrative legal reform, offering a deeper lens beyond procedural analysis. As a policy implication, the government should urgently issue implementing regulations, reestablish judicial review, and develop integrated technical guidelines to strengthen OSS-RBA's legal reliability and effectiveness.